Cyclodextrin-Based Nanosponges: Overview and Opportunities - Utzeri, Gianluca; Matias, Pedro M. C.; Murtinho, Dina; Valente, Artur J. M. (Frontiers in Chemistry, 2022)
Nanosponges are solid cross-linked polymeric nano-sized porous structures. This broad concept involves, among others, metal organic frameworks and hydrogels. This manuscript aims to focus on cyclodextrin-based nanosponges. Cyclodextrins are cyclic oligomers of glucose derived from starch. The combined external hydrophilicity with the internal hydrophobic surface constitute a unique “microenvironment”, that confers them the peculiar ability to form inclusion host‒guest complexes with many hydrophobic substances. These complexes may impart beneficial modifications of the properties of guest molecules such as solubility enhancement and stabilization of labile guests. These properties complemented with the possibility of using different crosslinkers and high polymeric surface, make these sponges highly suitable for a large range of applications. Despite of that, in the last two decades, cyclodextrin-based nanosponges have been developed for pharmaceutical and biomedical applications, taking advantage of the nontoxicity of cyclodextrins towards humans. This paper provides a critical and timely compilation of the contributions involving cyclodextrins nanosponges for those areas, but also paves the way for other important applications, including water and soil remediation and catalysis.